10(x-5)=-5(x+4)+30

Simple and best practice solution for 10(x-5)=-5(x+4)+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x-5)=-5(x+4)+30 equation:



10(x-5)=-5(x+4)+30
We move all terms to the left:
10(x-5)-(-5(x+4)+30)=0
We multiply parentheses
10x-(-5(x+4)+30)-50=0
We calculate terms in parentheses: -(-5(x+4)+30), so:
-5(x+4)+30
We multiply parentheses
-5x-20+30
We add all the numbers together, and all the variables
-5x+10
Back to the equation:
-(-5x+10)
We get rid of parentheses
10x+5x-10-50=0
We add all the numbers together, and all the variables
15x-60=0
We move all terms containing x to the left, all other terms to the right
15x=60
x=60/15
x=4

See similar equations:

| -8(s+5)=-100 | | 5(2x+3)-6(x-3)=47 | | 8(x-4)=4(x-9)+16 | | 7y+1+4y+14=180 | | 2(4×+3)=6x+14 | | 7y+1=4y+14 | | 7=m+1m= | | 4x+8=x-224x+8=x-22 | | x^2+6x=182-1/2x | | 38+5k=8k+33 | | 10h+9=86 | | -7+9x=11 | | 7x+4=40-5x | | 49+x^2=(5+x)^2 | | 7^2+x^2=(5+x)^2 | | 7(x+9)=-9(x-4)+27 | | -2+15x+21=79 | | 4x+5=16-7x | | x÷(-9)=6 | | 2z/9-6=7 | | 8x​ +3=2 | | 5^(3x-12)=125 | | 13y−5=9y+27. | | 2x+10=4x−10 | | 9h-30=50 | | 4x=3x+x+6* | | 7(9x-12)=105 | | 4(6y+4)+2(2y+5)=-2 | | 71=2x-13 | | 3(2b+1)–2b=6 | | 4(x+6)+4(2x+2)=8 | | 6x*2x=100 |

Equations solver categories